Reformasi Pendidikan Menghadapi Tantangan Abad 21 - Wita Anggraini; Hudaidah Hudaidah (Departement of Mathematics Education, 2021)
This article will focus on what kind of education system and human resources are needed in the next century. Based on this knowledge, several alternative solutions are provided to solve problems in our education system to